1991
DOI: 10.1177/009102609102000308
|View full text |Cite
|
Sign up to set email alerts
|

Creating New Approaches to Recognize and Deter Sabotage

Abstract: This paper examined a list of sabotage forms found in the workplace today, developed reasons for sabotage events. Data were gathered from 44 human resources managers and 164 super visors from 10 companies. Findings revealed that various forms of sabotage have subtly blended into the work routine-deliberate absenteeism, slowing down production, working without enthusiasm, and consistent turnover. The findings direct human resources managers to observe worker conflict, and help reduce tension-causing situations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
3

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 2 publications
1
5
0
3
Order By: Relevance
“…As managers' dishonesty significantly predicted powerlessness in this study, managers' dishonesty can indeed become an obstacle to firm performance because when powerlessness increases (i.e., lack of control over their work), followers undermine the processes that support the core activity or technical core of the bank. This result is consistent with prior research suggesting that individuals who feel powerless could engage in sabotage (DiBattista, ; Bennett, ), which would enhance individuals' sense of control over their work (Allen and Greenberger, ).…”
Section: Discussionsupporting
confidence: 91%
“…As managers' dishonesty significantly predicted powerlessness in this study, managers' dishonesty can indeed become an obstacle to firm performance because when powerlessness increases (i.e., lack of control over their work), followers undermine the processes that support the core activity or technical core of the bank. This result is consistent with prior research suggesting that individuals who feel powerless could engage in sabotage (DiBattista, ; Bennett, ), which would enhance individuals' sense of control over their work (Allen and Greenberger, ).…”
Section: Discussionsupporting
confidence: 91%
“…In addition to developing leaders who foster positive employee relations, HRM can support positive management relations by looking out for worker conflict and intervening where appropriate to avoid negative outcomes, such as deliberate acts of sabotage (DiBattista, 1991). DiBattista found that a significant number of sabotage events (e.g., employee theft, infecting computers with virus', contaminating water supply, and strikes) resulted from labor disputes.…”
Section: Interrelationships and Employee-organization Dynamicsmentioning
confidence: 99%
“…Counterproductive behaviors were generally investigated in international literature (Appelbaum and Roy-Girard, 2007:22;Bolton et al, 2010:538;Appelbaum and Shapiro, 2006:14;Branch, 2008:4;Martinko et al, 2002:36;Ferris et al, 2009:279). However, negative behavior in workplace has different studies in the literature as transferred by Güllü and Şahin such as revenge (Bies, Tripp and Kramer, 1997), organizational deviance (Berry et al, 2007) , counterproductive work behaviors (Fox et al, 2007), mobbing (Leymann,1996), workplace terror (Neuman and Baron, 1998), workplace violence (Rogers and Kelloway, 1997), retaliation (Skarlicki and Folger, 1997), organizational sabotage (Di Battista, 1991;Ambrose et al, 2002), antisocial behaviors (Giacalone and Greenberg, 1997).…”
Section: Literaturementioning
confidence: 99%